(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s
(3ChdgG (B:s
(3CNHGQ CHj fNjdI hfSHg, Hbhdg(B: (3CHhfNjdI CSeg dG cfjJg, hjcaj CHG GdLfjO, PcQ GdCUeYj Pdc, hCHhYeQh GdTjHGfj hGHf MHjH, dG jYQa dg GSe ZjQg s
(3BNQgG (B:s
(3gh GdbMja Hf MejQ CMO Hfj bjS Hf NaGLI Hf Ybjd Hf cYH Hf QHjYI Hf YGeQ Hf UYUYI, TGYQ ebd ef TYQGA GdESdGe s
(3GdfSNI HgG MhGTs
(3Ydi UaMI GdYfhGf agQSJ HCSeGA GdoeJQnLe dge hdcfg jMhj CSeGA ZjQ ehLhOI aj GdcJGH JeKd KdK gPG GdagQSJs
(3ef fSNI YGTQI hYdjgG JUMjMGJs
(3hQO CjVkG JMJ Qbe (B2176 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B78s
Keywords: (3GdCOHs